Effect of Zinc and Iron on Yield and Yield Attributes of Rainfed Cowpea (Vigna unguiculata L. Walp) - Patel, M M; Patel, I C; Patel, R L; Acharya, S (Annals of Arid Zone, 2016)
A field experiment was conducted during kharif seasons of 2002, 2003 and 2005 to study the effect of zinc and iron on yield and yield attributes of rainfed cowpea (Vigna unguculata L. Walp) at Main Pulses Research Station, S.D. Agricultural University, Sardarkrushinagar on loamy sand soil. The results revealed that the application of ZnSO4@ 25 kg ha-1 through soil proved to be most effective and increased the seed yield by 43.0% when compared with control followed by the spraying of 0.5% ZnSO4 at 25 and 45 DAS. The increase in yield was due to increase in number of pods per plant, 100-seed weight and number of branches per plant. The highest net return (Rs. 13,114 ha-1) and benefit cost ratio (1.97) were obtained with soil application of ZnSO4 @ 25 kg ha-1. Key wards: Cowpea, ZnSO4, FeSO4, rainfed, net return.